If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 3u + 1 Reorder the terms: 10 = 1 + 3u Solving 10 = 1 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 10 + -3u = 1 + 3u + -3u Combine like terms: 3u + -3u = 0 10 + -3u = 1 + 0 10 + -3u = 1 Add '-10' to each side of the equation. 10 + -10 + -3u = 1 + -10 Combine like terms: 10 + -10 = 0 0 + -3u = 1 + -10 -3u = 1 + -10 Combine like terms: 1 + -10 = -9 -3u = -9 Divide each side by '-3'. u = 3 Simplifying u = 3
| -4(x-12)-2=6 | | 3y-2+2y+7-y= | | 8x^2+5=12x | | x+g=21 | | 4(-2y+3)= | | 119+9-3a=-7 | | 5x-1x+3=5 | | 8x-4=15x-18 | | 8=-7+y | | 10b^3+4b^2= | | 3-6b+13=26 | | Z^2+-9Z+18=0 | | Logs=0.06 | | 1520=38(p+10) | | -8-5x-4x=3x+4 | | 5s^2-16s=0 | | 11(-28)-20=28 | | 7-2d=4-6-3d | | 5(x-2)=4-(14+8x) | | 22-41= | | 8x-10x+3=0 | | 855=5x+855 | | log(x+2)=log(3x+3) | | 5x^21/10x^7 | | s*5-21=54 | | Z*Z-9z+18=0 | | 19(.1860465116)=x | | 2t+5=t | | 4.3x=.8 | | -8d-7-5d+9+d= | | 5x^2-3=-9 | | -12x+30y+0=0 |